2021
DOI: 10.3389/fgene.2021.801218
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of HSF Genes From Secale cereale and its Triticeae Relatives Reveal Ancient and Recent Gene Expansions

Abstract: Plants have evolved sophisticated systems to cope with the environmental stresses, with the heat shock factor (HSF) family proteins composing an integral part of the transcriptional regulation system. Understanding the evolutionary history and functional diversity of HSFs will facilitate improving tolerance of crops to adverse environmental conditions. In this study, genome-wide analysis of Secale cereale identified 31 HSF genes. The total number of HSF genes in S. cereale is larger than that in barley and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Large fluctuations in environmental temperature caused by inconstant global climate also render severe abiotic impacts (heat and cold stress) on plants. To cope with such conditions, gene inventions and expansions of heat/cold shock factor gene families into plant genomes are constantly happening during adaptive evolution (Wang et al, 2018;Li et al, 2021). In this study, we have also detected in tested plant genomes a wide Phylogenetic tree of metal resistance proteins in plant genomes originated from microbial taxa.…”
Section: Hgt Genes In Response To Heat and Cold Stressmentioning
confidence: 84%
See 1 more Smart Citation
“…Large fluctuations in environmental temperature caused by inconstant global climate also render severe abiotic impacts (heat and cold stress) on plants. To cope with such conditions, gene inventions and expansions of heat/cold shock factor gene families into plant genomes are constantly happening during adaptive evolution (Wang et al, 2018;Li et al, 2021). In this study, we have also detected in tested plant genomes a wide Phylogenetic tree of metal resistance proteins in plant genomes originated from microbial taxa.…”
Section: Hgt Genes In Response To Heat and Cold Stressmentioning
confidence: 84%
“…Large fluctuations in environmental temperature caused by inconstant global climate also render severe abiotic impacts (heat and cold stress) on plants. To cope with such conditions, gene inventions and expansions of heat/cold shock factor gene families into plant genomes are constantly happening during adaptive evolution ( Wang et al., 2018 ; Li et al., 2021 ). In this study, we have also detected in tested plant genomes a wide range (26 gene entries) of microbial-originated HGT gene families related to heat/cold shock response ( Table 2 ), which mainly function as transcription factors and molecular chaperones regulated by the former, working corporately to maintain cellular protein homeostasis ( Andrási et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Hsps are found in the cytoplasm and nucleus and are essential components for maintaining cellular homeostasis under adverse conditions, such as drought, cold, and high temperature, and Hsp20 acts as a molecular chaperone by binding to partially folded or denatured proteins to prevent the irreversible aggregation of proteins and to maintain stability (Eyles and Gierasch, 2010 ). Hsf transcription factors not only help organisms resist high temperatures, but also promote seed maturation and root growth (Li et al, 2021 ). Therefore, it is hypothesized that DGL1 can improve the stability of plant cells in an adversarial environment by inducing the expression of genes during the plant response to thermal stimulation.…”
Section: Results and Analysismentioning
confidence: 99%
“…Large fluctuations in environmental temperature, resulting from solar radiation overexposure and changing global climate patterns, can impose significant abiotic stress on the phyllosphere of plants, leading to heat and cold stresses. To cope with these challenges, gene expansions have been observed in heat/cold shock factor gene families during adaptive evolution ( Wang et al., 2018 ; Li et al., 2021 ). In our study, we identified a specific set of gene orthogroups (171 gene entries) associated with the heat/cold shock response in the metagenome of the tobacco phyllosphere ( Figure 3B and see Table S1 at https://doi.org/10.6084/m9.figshare.21257352.v1 ).…”
Section: Resultsmentioning
confidence: 99%